Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Lyu, Mingxin; Gao, Xiaolong; Zhang, Mo; Lin, Shihui; Luo, Xuan; You, Weiwei; Ke, Caihuan (Frontiers in Marine Science, 2021)
Abalone (Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms (P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea, but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai. The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX2R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea. These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.